Domesticity under siege when home isn't safe - Taylor, Mark; Downey, Georgina; Meade, Terry (Bloomsbury VISUAL ARTS, 2022)
"Theories of the domestic stemming from the 19th century have focused on the home as a refuge and place of repose for the family, a nurturing environment for children and a safe place for visitors. Under this conception, domestic space is positioned as nurturing and private, a refuge and place of retreat which gave rise to theories of 'home as haven'. While, arguably, some social conditions might suggest this is the case, Domesticity Under Siege exposes a different world, one in which the boundaries of nurturing domesticity collide with both outside and inside agents. Whether these agents are external military forces, psychological trauma or familial violence, they re-position meta-narratives of domesticity, not through identity politics or specialized subgroup experience, but relative to the actions of the world around an inhabited domain. That is, when home is constituted as a private realm, a place where individuals or groups can reside in 'safety and comfort', it is argued as a place in which the individual exercises control or power. However, there are many occasions when forces act upon the home and threaten aspects of safety and comfort, often through such things as ruination, violence, mortality, and infestation. Organised around four thematic sections, 'Microbes, Animals and Insects', 'Human Agents', Wars and Disasters as Agents' and 'Hauntings, Eeriness and the Uncanny', chapters provide a range of approaches to the home which challenge notions of 'haven' and reflect major causes that have played an important role in undermining the modern home. Examples and case studies explore the domestic screen, hoarding, hauntings, violence and imprisonment in the home, wartime interior art, the Hanover Merzbau and Wolfgang Staudte's 1946 film Die Mörder sind unter uns ('The Murderers are Among Us')."--